2021
DOI: 10.1111/jnc.15493
|View full text |Cite
|
Sign up to set email alerts
|

MEC17‐induced α‐tubulin acetylation restores mitochondrial transport function and alleviates axonal injury after intracerebral hemorrhage in mice

Abstract: Injury to long axonal projections is a central pathological feature at the early phase of intracerebral hemorrhage (ICH). It has been reported to contribute to persistent functional disability following ICH. However, the molecular mechanisms that drive axonal degeneration remain unclear. Autologous blood was injected into the striatum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(59 reference statements)
2
12
0
Order By: Relevance
“…Several studies including ours have pointed to the validity of this approach. For example, targeting MTs by increasing their acetylation, which is frequently linked to MT stability, protects axons and transport of mitochondria in a mouse trauma model caused by intracerebral haemorrhage (Yang et al, 2022). Furthermore, manipulation of MTs by the use of MT-targeting agents (MTAs) has proven valuable in the context of age-related neurodegenerative diseases, as suggested by recent reports highlighting the beneficial therapeutic effects of MT-stabilising compounds such as Epothilone D in several models of tauopathies (Varidaki et al, 2018, Fernandez-Valenzuela et al, 2020, Wordeman and Vicente, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies including ours have pointed to the validity of this approach. For example, targeting MTs by increasing their acetylation, which is frequently linked to MT stability, protects axons and transport of mitochondria in a mouse trauma model caused by intracerebral haemorrhage (Yang et al, 2022). Furthermore, manipulation of MTs by the use of MT-targeting agents (MTAs) has proven valuable in the context of age-related neurodegenerative diseases, as suggested by recent reports highlighting the beneficial therapeutic effects of MT-stabilising compounds such as Epothilone D in several models of tauopathies (Varidaki et al, 2018, Fernandez-Valenzuela et al, 2020, Wordeman and Vicente, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 30 Changes in the axonal cytoskeleton after ICH not only impact the physical structure of the axon but also mitochondrial transport and function leading to degeneration. 31 Recent studies have suggested that the inhibition of histone deacetylases (HDACs) with scriptaid or conditional knockout of HDAC2 in microglia can reduce ICH-induced neuroinflammation and WM injury in mice. 32 Other studies have targeted neuroinflammation with the antibiotic and inhibitor of microglial activation minocycline in piglets, 33 and the sphingosine-1-phosphate receptor modulator FTY720/fingolimod in mice.…”
Section: Haematomamentioning
confidence: 99%
“…AVM, arteriovenous malformations; BBB, blood-brain barrier; CAA, cerebral amyloid angiopathy; CCM, cerebral cavernous malformation; COL4A1, α1 chain of collagen type IV; ICH, intracerebral haemorrhage; L-NAME, N ω -nitro-L-arginine methyl ester. (A) Rodent models Model Aetiological or pathophysiological mechanisms addressed, translational value Autologous blood injection Endogenous haematoma clearance 26 , 28 , 29 , 53 White matter injury and axonal degeneration 30 , 100 Cell death 29 , 51 , 101 , 102 Perihaematomal oedema 49 , 51 , 53 , 101 , 102 BBB impairment 22 , 45 , 47 , 49 Inflammation 28 , 49 , 51 , 52 , 53 , 101 , 102 , 103 Immunosuppression 58 Cardiac complications 63 , 64 Can be combined with comorbidities: angiotensin II infusion + hyperglycaemia (incl. haematoma expansion), 22 hyperglycaemia 102 Collagenase injection Anticoagulation 12 , 13 Endogenous haematoma clearance 26 , …”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%
“…Evaluation of ATP Levels. ATP in tissues around the haematoma and culture cells was measured using an ATP assay kit (ab83355; Abcam) as described previously [30]. Briefly, tissues or cells were washed in cold PBS, homogenised, and centrifuged to collect the supernatant, and the samples were mixed with assay buffer.…”
Section: Mitochondrial Membrane Potential and Mitochondrialmentioning
confidence: 99%